Review of “Minority Language Writers in the Wake of World War One. A Case Study of Four European Authors” by Jelle Krol, Palgrave Studies in Minority Languages and Communities. Palgrave Macmillan 2020, 346 pp - Listewnik, Marta (Studia Celtica Posnaniensia, 2021)
Review: “Minority Language Writers in the Wake of World War One. A Case Study of Four European Authors” by Jelle Krol, Palgrave Studies in Minority Languages and Communities. Palgrave Macmillan 2020, 346 pp. Review by Marta Listewnik, PhD, Adam Mickiewicz University in Poznań.